Response of cardiac pulse parameters in humans at various inclinations via 360° rotating platform for simulated microgravity perspective - Jagtap, Sagar; Kumar, Ajay; Mahale, Bhoopesh; Dixit, Jyotsana; Kalange, Ashok E.; Kanawade, Rajesh; Gangal, Shashikala; Vidyasagar, Pandit (NPJ Microgravity, 2023)
On the Earth, the human body is designed and adapted to function under uniform gravitational acceleration. However, exposure to microgravity or weightlessness as experienced by astronauts in space causes significant alterations in the functioning of the human cardiovascular system. Due to limitations in using real microgravity platforms, researchers opted for various ground-based microgravity analogs including head-down tilt (HDT) at fixed inclination. However, in the present study, an investigation of response of various cardiac parameters and their circulatory adaptation in 18 healthy male subjects was undertaken by using an indigenously developed 360 & DEG; rotating platform. Cardiac pulse was recorded from 0 & DEG; to 360 & DEG; in steps of 30 & DEG; inclination using piezoelectric pulse sensor (MLT1010) and associated cardiac parameters were analyzed. The results showed significant changes in the pulse shape while an interesting oscillating pattern was observed in associated cardiac parameters when rotated from 0 & DEG; to 360 & DEG;. The response of cardiac parameters became normal after returning to supine posture indicating the ability of the cardiovascular system to reversibly adapt to the postural changes. The observed changes in cardiac parameters at an inclination of 270 & DEG;, in particular, were found to be comparable with spaceflight studies. Based on the obtained results and the proposed extended version of fluid redistribution mechanism, we herewith hypothesize that the rotation of a subject to head down tilt inclination (270 & DEG;) along with other inclinations could represent a better microgravity analog for understanding the cumulative cardiac response of astronauts in space, particularly for short duration space missions.